KELAS REPERTOAR PADA PEMBELAJARAN GITAR - Herwin Yogo Wicaksono (Imaji, 2006)
Repertoire classes have not become a common practice in manyinformal institutions conducting guitar learning even though some formalinstitutions have done the practice. To implement repertoire classes needsappropriate time and places.Repertoire classes regularly conducted are proven to improve students’motivation to learn, decrease their nervousness and increase their selfconfidence.Besides, such classes motivate them to compete in improving theirskill and become places to socialize among them.Key words: repertoire, guitar learning and students' self confidence